Hubungan Antara Kohesivitas Kelompok Dengan Komitmen Organisasi Mahasiswa Anggota Baru Unit Kegiatan Mahasiswa (Ukm) Bidang Kesenian di Universitas Negeri Malang - Amalia Roshanty; Fattah Hidayat; Gamma Hakim (Flourishing Journal, 2021)
Students Organizations is an institution that accommodating students’ interests. In its process during the projects often appeared to be something controversial and takes it into a further discussion among them and apparently impacted to the organizations’ existence. It happened for its low group cohesiveness and organizational commitment among the Students Organization members. Therefore, the researcher interested to find out about whether there is correlation or not between group cohesiveness and organizational commitment among the student’s organization members of Art sector in State University of Malang. Descriptive qualitative was the method employed in this research using purposive sampling technique in gaining the samples. The subject was 60 of student’s organization new field of art members in State University of Malang. The instrument used in this research were group cohesiveness scale and scale of organizational commitment. Before the data was analyzed, the researcher did a normality test through Kolmogorov-Smirnov formula which shown that the group cohesiveness is not distributed normally, and the scale of organizational commitment is distributed normally. So that the researcher, in this research, did a non-parametric correlation analysis through Spearman’s formula. The result of the data analysis shows that there is positive relation between group cohesiveness and organizational commitment among students’ organization new field of art members in State University of Malang (ρ together with 0.893, sign together with 0.000, α less than 0.05). Through this analysis, the result shows that there is a good and high relation between group cohesiveness and organizational commitment. According to the result of the research, it is suggested that (1) all the board of the committees to be aware of increasing the cohesiveness among the new members and creating routinized group activities in order to increase organizational commitment, (2) all the members are supposed to show high acceptance and respects to each other in the organization, actively involved in every activities, loyal to the organization, responsible to the task given, and come on time in every activity in order to enhance the group cohesiveness, and also (3) to the further researcher are expected to evolve the previous research , such as developing the scale, adding the variable or population of the research, in order to improve the organization existence. Unit Kegiatan Mahasiswa (UKM) merupakan lembaga organisasi mahasiswa intra kampus. Sering kali ada beberapa perbedaan pendapat dalam UKM. Hal tersebut dapat terjadi karena rendahnya kohesivitas kelompok dan komitmen organisasi dari anggota baru UKM. Peneliti ingin mengetahui adakah hubungan antara kohesivitas kelompok dengan komitmen organisasi pada mahasiswa anggota baru UKM bidang minat kesenian di Universitas Negeri Malang dengan menggunakan deskriptif kuantitatif dan teknik purposive sampling untuk pengambilan sampel. Subjek penelitian ini sejumlah 60 mahasiswa anggota baru UKM kesenian di Universitas Negeri Malang. Instrumen dalam penelitian ini menggunakan skala kohesivitas kelompok dan skala komitmen organisasi. peneliti melakukan uji normalitas dengan formula Kolmogorov-Smirnov.  pada penelitian ini peneliti melakukan analisis korelasi non-parametrik menggunakan formula Spearman. Hasil analisis data menunjukkan ada hubungan yang positif antara kohesivitas kelompok dengan komitmen organisasi pada mahasiswa anggota baru UKM (ρ sama dengan 0.893, sign sama dengan 0.000, α kurang dari 0.05). Hubungan yang terbentuk adalah kohesivitas kelompok dan komitmen organisasi berada dalam kategori sangat tinggi. Saran penelitian adalah (1) para pengurus UKM untuk dapat membangun kohesivitas dari anggota baru UKM dengan mengadakan kegiatan rutin yang bersifat berkelompok, (2) para anggota untuk dapat membangun kohesivitas kelompok dengan cara mampu menunjukkan penerimaan tehadap anggota lain, aktif dalam setiap kegiatan, memiliki loyalitas terhadap UKM, bertanggungjawab terhadap pekerjaan, dan hadir tepat waktu di kegiatan, serta (3) pada peneliti selanjutnya untuk dapat melakukan tindak lanjut penelitian seperti pengembangan alat ukur, penambahan variabel atau populasi penelitian untuk dapat mengembangkan organisasi.